Antitumor Activity of Ionic Liquids Based on Ampicillin. Issue 9 (16th July 2015) - Ferraz, Ricardo; Costa‐Rodrigues, João; Fernandes, Maria H.; Santos, Miguel M.; Marrucho, Isabel M.; Rebelo, Luís Paulo N.; Prudêncio, Cristina; Noronha, João Paulo; Petrovski, Željko; Branco, Luís C.
Abstract Significant antiproliferative effects against various tumor cell lines were observed with novel ampicillin salts as ionic liquids. The combination of anionic ampicillin with appropriate ammonium, imidazolium, phosphonium, and pyridinium cations yielded active pharmaceutical ingredient ionic liquids (API‐ILs) that show potent antiproliferative activities against five different human cancer cell lines: T47D (breast), PC3 (prostate), HepG2 (liver), MG63 (osteosarcoma), and RKO (colon). Some API‐ILs showed IC50 values between 5 and 42 nM, activities that stand in dramatic contrast to the negligible cytotoxic activity level shown by the ampicillin sodium salt. Moreover, very low cytotoxicity against two primary cell lines—skin (SF) and gingival fibroblasts (GF)—indicates that the majority of these API‐ILs are nontoxic to normal human cell lines. The most promising combination of antitumor activity and low toxicity toward healthy cells was observed for the 1‐hydroxyethyl‐3‐methylimidazolium–ampicillin pair ([C2OHMIM][Amp]), making this the most suitable lead API‐IL for future studies.